A multi‐functional genetic manipulation system and its use in high‐level expression of a β‐mannanase mutant with high specific activity in Pichia pastoris. Issue 4 (4th May 2021) - Liu, Zhemin; Cao, Linyuan; Fu, Xiaodan; Liang, Qingping; Sun, Han; Mou, Haijin
Summary: To further extend the practical application of a thermostable and acidic resistance β‐mannanase (ManAK) in animal feed additives, an effective strategy that combined directed evolution and metabolic engineering was developed. Four positive mutants (P191M, P194E, S199G and S268Q) with enhanced specific activity (25.5%–60.9%) were obtained. The S199G mutant exhibited 56.7% enhancement of specific activity at 37°C and good thermostability, and this was selected for high‐level expression in P. pastoris X33. A multi‐functional and scarless genetic manipulation system was proposed and functionally verified (gene deletion, substitution/insertion and point mutation). This was then subjected to Rox1p (an oxygen related transcription regulator) deletion and Vitreoscilla haemoglobin (VHb) co‐expression for high enzyme productivity in P. pastoris X33VIIManAK S199G . An excellent strain, named X33VIIManAK S199G ∆ rox1 ::VHb, was achieved by combining these two factors, and then the maximum enzymatic activity was further increased to 3753 U ml ‐1, which was nearly twice as much as the maximum production of ManAK in P. pastoris . This work provides a systematic and effective method to improve the enzymatic yield of β‐mannanase, promotes the application of ManAK in feed additives, and also demonstrated that a scarless genetic manipulation tool is useful in P. pastoris . Abstract : Four β‐mannanase mutants with enhanced specific activity were achieved by directed evolution. A scarless genetic manipulation system was proposed and functionally verified. High‐level expression of enzyme was achieved by oxygen related metabolic pathway optimization.